Making Participatory Policy in Building Tourist Village Governance in Klungkung Regency, Bali, Indonesia - I Ketut Sudiarta; I Made Suwitra; I Ngurah Suryawan (Randwick International of Social Science Journal, 2022)
This research was conducted with the aim of knowing: (1) Characteristics of resources as a core attraction for the development of marine ecotourism that is unique to a specific location in Bali along with the pattern or practice of its implementation, (2) The suitability of ecotourism principles with Balinese local wisdom, and (3) Attributes of the ecotourism principle which are strengths and weaknesses in the implementation of local Balinese marine ecotourism .This research was designed with mixed methods. Sources of data are diving ecotourism destinations, traditional village administrators, and diving communities in diving ecotourism destinations which were collected by survey method. Attributes that become strengths in the implementation of ecotourism with local Balinese wisdom that need to be maintained and improved performance are: 1) Respect for good local culture and wisdom, (2) Application of Standard Operating Procedures to minimize negative impacts on biodiversity and the environment, (3) Responsibility moral, ethical and behavioral responsibility towards the natural and cultural environment, and (4) Respect, courtesy, and friendliness to tourists. While the attributes that are weaknesses and need to be prioritized for improving their performance are: (1) Building awareness about the preservation of culture and local wisdom, (2) Use and operation of tourism facilities that have a low impact on the natural environment, (3) Minimization of social impacts, behavior and psychology in the community, (4) Partnership and involvement of local community participation, (5) Use of local products, (6) Guidance on ecotourism as a diversification of the local economy, (7) Use of local labor, and (8) Capacity building and skills of local communities.In order to realize competitive marine ecotourism, local Balinese wisdom, and sustainability.